Static Voltage Stability Region Considering Limit Induced Bifurcation - Daobing LIU; Yue QI; Shichun LI; Miaosheng BAO; Yingying GUO; Juecen LI (Zhongguo dianli)
With the widespread application of a high percentage of renewable energy in power systems, the volatility and randomness of renewable energy pose challenges for static voltage stability assessment of power systems. The static voltage stability region (SVSR) of power systems can comprehensively analyze and monitor the voltage stability of power systems. The key is to construct the stability region boundary quickly and accurately. To address the problems of large computational effort of the traditional continuous power flow method and nonlinear programming method, an SVSR boundary construction optimization model based on the topological properties of SVSR boundaries is proposed, in which the adjacent boundary points are directly calculated from known boundary points by a prediction-correction method based on the property that the boundaries are continuous and smooth. Based on this model, a limit induced bifurcation (LIB) identification method is proposed to construct the SVSR boundary considering LIB. Finally, the feasibility and accuracy of the proposed method are verified by case analysis.